MAPPING PM2.5 POLLUTION ZONES IN NIGERIA USING HIERARCHICAL CLUSTERING - Yohanna, Emmanuel; Jasini, Waida; Yila Yusuf, Emmanuel (FUDMA Journal of Sciences, 2025)
The persistent challenges in Nigeria’s air-quality monitoring network have limited large-scale spatial assessments of particulate matter. This study conducts a national-scale clustering analysis of PM2.5 using agglomerative hierarchical clustering which does not require a pre-specified number of clusters and shows hierarchical linkages across monitoring sites. Ward’s method was applied to daily PM2.5 data from 15 monitoring stations over the period from 2019 to 2023, using Euclidean distance to assess the similarity measure. Three distinct clusters were identified: High Pollution Regions (HPR) with an average PM2.5 concentration of 61.7 µg m⁻³, Medium Pollution Regions (MPR) at 46.7 µg m⁻³, and Low Pollution Regions (LPR) at 36.0 µg m⁻³. The 2019 haze episode produced peak concentrations of 197.7 µg m⁻³ in HPR, leading to a hazardous Air Quality Index (AQI) of 273. Cluster distributions demonstrated a significant correlation with land-use characteristics. HPR stations were primarily situated in industrial zones, MPR in densely built urban corridors, and LPR in coastal peri-urban regions. The resulting novel spatial stratification offers substantial evidence for developing targeted and regionally adaptive air quality management strategies across Nigeria.